The Potential Use of Wild Swamp Vegetables Through an Ethnobothanical Survey - Sasi Gendro Sari; Fidhi Widya Sari; Eny Dwi Pudjawati (Journal of Wetlands Environmental Management, 2020)
Swamp areas provide basic needs for local communities living in wetland areas, especially in the Banjar regency, South Kalimantan. Indigenous people called Banjarese or the Banjar are consuming wild swamp vegetables and processing them into traditional food combined with rice. The potential use of swamp plants for vegetables by Banjarese was investigated through an ethnobotanical study. The vegetables were obtained from three selected lowland swamps located in three villages of Banjar regency namely Panjambuan, Sungai Batang and Sungai Tuan Ilir. Wild swamp vegetables were identified using a semi structured questionnaire technique and the 72 key respondents were selected by a purposive sampling based on their interaction with swamps. Then they were classified into gender, and 4 groups based on their ages to determine knowledge level (Mg) in utilizing wild swamp vegetables. After that, their level knowledge was tested based on gender and ages using Kruskal Wallis test. Mann Whitney U-test was applied to distinguish the difference of knowledge level from ages and sex. The findings observed were six wild swamp vegetables used by Banjarese such as water spinach Ipomoea aquatica, genjer Limnocharis flava, hairy water lily Nymphaea pubescens, water mimosa Neptunia oleracea, taro Colocasia esculenta and swamp fern Stenochlaena palustris. All parts of the plants were used except for the roots. Leaves were preferably cookedwith 44,5% in comparison toother parts of plants like stem, flower, tendril and corm. Water spinach was frequently consumed by Banjarese compared to other plants. The knowledge level of local people was 67,84 categorized as a middle level and an elderly more than 60 years old had the highest knowledge level in using swamp plants compared to other groups. Moreover, women had better knowledge rather than men to utilize wild swamp plants for food.